An innovative drug for the treatment of respiratory infections - V. A. Petrov (Лечащий Врач)
The review is devoted to the urgent problem of world health – acute respiratory diseases. This is the most common group of diseases in the human population. Regardless of the type of pathogen, acute respiratory disease manifests itself with similar symptoms, of different duration and severity. More often, respiratory pathogens affect the upper respiratory tract and are limited to the development of catarrhal manifestations with a typical clinical picture in the form of fever, general non-specific/flu-like symptoms and intoxication syndromes. The review presents the results of experimental and clinical studies of a new antiviral drug with antibacterial activity. The drug affects key targets involved in the process of recognizing an infectious pathogen, triggering an immune response and eliminating the pathogen. A series of preclinical studies have demonstrated the efficacy of the drug in viral and mixed viral-bacterial infections. Pharmacological effects of new drug include antiviral, immunotropic, antibacterial and anti-inflammatory activity. The antiviral efficacy of drug components (technologically processed antibodies to IFN-gamma and CD4 receptor) has been previously demonstrated by numerous studies and confirmed by long-term experience with the use of precursors. The new components included in the composition of the drug directly affect the molecules of the major histocompatibility complex and provide not only an increase in the antiviral effect, but also an antibacterial effect. Drug own antibacterial effect was noted, as well as its ability to increase the efficacy of therapy when used in combination with an antibacterial drug. The results of clinical studies have shown the ability to significantly reduce the duration of acute respiratory viral infection and prevent the development of bacterial complications. In the reviewed works, positive data on a favorable safety profile of the drug were obtained. It is considered appropriate to continue clinical studies of the drug in adult and pediatric populations (including children aged 12-18 years).